Efektivitas Pengobatan pada Pasien Penyakit Paru Obstruksi Kronis (PPOK) di Rumah Sakit Wilayah Yogyakarta - Chynthia Pradiftha Sari; Suci Hanifah; Rosdiana Rosdiana; Yuni Anisa (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Chronic Obstructive Pulmonary Disease (COPD) is a complex respiratory disorder that requires multiple approaches to assess treatment response, no specific therapy can stop the progression of disease cure. This study aimed to measure the response of COPD treatment in outpatients at Hospitals in Yogyakarta. The study was designed descriptive observational cross-sectional involved COPD outpatients in July 2018 - June 2019 (N = 156). Inclusion criteria the subjects: age> 40 years, without other respiratory diseases (asthma, lung cancer), took theophylline for at least the last one month, complete the CAT questionnaire, and sign an informed consent. Data collected were characteristics of respondents, treatment profile (exacerbation, maintenance), and response therapy data. Evaluation of treatment response was measured using the COPD Assessment Test (CAT) questionnaire and classified the response into effective, quite effective, and not effective. These data were then presented in form of percentage distribution. The results showed that an exacerbation study with single bronchodilator 39.10%, and a combination of bronchodilator with other bronchodilators 60.90%, most LABA-ICS / LAMA rescue therapies (48.72%). Results of evaluation the use of LABA-ICS / LAMA / Methylxanthine (18.59%), LABA-ICS / LAMA / Methylxanthine/ Mucolytic (11.54%), LABA-ICS / LAMA / SABA / Methylxanthine / Mucolytic (9.62%) )) gave a fairly effective treatment response (CAT score ≥10-19) 50.64%, effective (CAT score <10) 47.43%, ineffective (CAT score ≥20) 1.93%.